Pengaruh Gaya Kepemimpinan Kepala Unit Terhadap Kinerja Unit Turjawali Satlantas Polres Pati Dalam Mewujudkan Kamseltibcar Lantas - Herawati , Elia (Indonesian National Police Academy, 2017)
Turjawali Unit is a unit or leading organization in performing their duties and functions in the field of traffic safety, especially in realizing the smoothness of traffic safety order. Each success or failure of Turjawali Unit in carrying out its duties and functions, inseparable from the role and leadership of the Chief of Turjawali Unit. Less of proper leadership style is suppose to be the cause of less of motivation and spirit of the members to work maximum so the style of leadership is the source of some problems that arise in organizations. The purpose of this research is to determine and analyze the effect of leadership style that consists of 4 types, participate leadership style, Leader-Member Exchange (LMX), transactional and transformational of performance Turjawali Unit Traffic Pati Police Resort in realizing security, safety, order, smoothness of traffic. The research of methodology using descriptive statistical analysis and multiple linear regression analysis by F test and t test. Data processing using SPSS 16.0 for Windows. The population in this research are members of Turjawali Unit Traffic Pati Police Resort as a sample of 37 people, the determination of jenuh samples is using sampling techniques. Data collection with questionnaires, interviews, and documentation. The results obtained by the simultaneous regression coefficient of Fhitung = 30.490 greater than Ftabel = 2,701, so the participative leadership style, Leader-Member Exchange (LMX), transactional and transformational influence simultaneously on the performance Turjawali Unit Traffic Pati Police Resort. On research of coefficient partially obtained thitung participate leadership style 1.987, Leader-Member Exchange (LMX) 1.936, transactional (-2.342), and transformational 6.505, all calculations except transformational leadership style show thitung is smaller than ttable = 2.045, meaning that each the independent variables (leadership style) less partial effect on the dependent variable (performance of members). Transformational leadership style is the most dominant leadership style in influencing the performance of Turjawali Unit Traffic Pati Police Resort in realizing security, safety, order, smoothness of traffic.